2015
DOI: 10.1155/2015/352478
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of FOXM1 in Patients with Malignant Solid Tumor: A Meta-Analysis and System Review

Abstract: Forkhead box M1 (FOXM1), a member of the Fox transcription factors family, was closely related with cell cycle. FOXM1 played an important role in MST and prompted a poor prognosis for MST patients. However, there were also some studies revealing no significant association between the FOXM1 expression and prognosis of patients. Therefore, we conducted meta-analysis to investigate whether the expression of FOXM1 was associated with MST prognosis. We collected 36 relevant studies through PubMed database and obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 69 publications
(68 reference statements)
1
55
0
Order By: Relevance
“…Additionally, we found that FOXM1 expression was significantly associated with larger tumor size, higher histological grade, lymph node metastasis, and intrinsic molecular subtypes, which is in line with the literature on female breast cancer and other cancer types [31,43]. Furthermore, FOXM1 expression highly correlated with a high Ki-67 proliferation index (p < 0.001); therefore, we could show that FOXM1 is a proliferation-associated protein in male breast cancer.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, we found that FOXM1 expression was significantly associated with larger tumor size, higher histological grade, lymph node metastasis, and intrinsic molecular subtypes, which is in line with the literature on female breast cancer and other cancer types [31,43]. Furthermore, FOXM1 expression highly correlated with a high Ki-67 proliferation index (p < 0.001); therefore, we could show that FOXM1 is a proliferation-associated protein in male breast cancer.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, overexpression of FOXM1 has been reported in a wide range of cancers, namely breast cancer, lung cancer, ovarian cancer, prostate adenocarcinoma, testicular cancer, bladder cancer, and colorectal cancer [17,42]. In general, high FOXM1 expression is recognized as an indicator of poor prognosis [43]. Numerous studies reported that FOXM1 overexpression correlated with tumor histological grade or stage and incidence of metastasis, and inversely correlated with OS [26,28,44].…”
Section: Discussionmentioning
confidence: 99%
“…Forkhead box M1 (FOXM1) is a transcription factor that has been implicated in cell growth and proliferation through control of cell‐cycle transition and apoptosis (Dai, Yang, Wang, Xiao, & Ruan, ) as a promising therapeutic target in various cancers (Z. Wang et al, ). Hence, recently herbal medicines (Bae et al, ; Safe & Kasiappan, ; Tariq et al, ) and natural compounds such as thiostrepton (Zhang et al, ) and casticin (Jiang et al, ) were reported to inhibit the transcriptional activity of FOXM1.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study suggested that FOXM1 could significantly downregulate the expression of P2cipi and P27kipi (7). During the transitional phase between G2 and M, two downstream target genes of FOXM1 were found to promote NF-κB to participate in the progression of neurodegenerative diseases, such as Alzheimer's disease and Parkinson's disease (20).…”
Section: Discussionmentioning
confidence: 99%
“…FOXM1 is expressed during the G1 and S phases in the cell cycle, and can regulate the transcription activity of numerous genes, including encoding cell division cycle (Cdc) 25A, Cdc25B, cyclin B, cyclin A, cyclin Dl, p21cip1, p27kipl, Aurora B kinase and Polo-like kinase 1. The loss of FOXM1 expression may lead to formation defects in the mitotic spindle and the delay of cell division, which may result in the failure of mitosis (7). FOXM1 is also associated with cell proliferation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%